A General Approach towards Catechol and Pyrogallol through Ruthenium‐ and Palladium‐Catalyzed CH Hydroxylation by Weak Coordination. Issue 7 (7th May 2014) - Yang, Xinglin; Sun, Yonghui; Chen, Zhang; Rao, Yu
Abstract An efficient ruthenium(II)‐ and palladium(II)‐catalyzed CH hydroxylation of aryl carbamates has been developed for the facile synthesis of catechols and pyrogallols. The reaction demonstrates excellent reactivity, regio‐ and chemoselectivity, good functional group compatibility and high yields. The practicality of this method has been proved by a gram‐scale synthesis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>